Employee empowerment and organizational commitment among employees of star-rated hotels in Ghana: Does perceived supervisor support matter? - Michael Kyei-Frimpong; Emmanuel Kodwo Amoako; Bridget Akwetey-Siaw; Kwame Owusu Boakye; Isaac Nyarko Adu; Abdul-Razak Suleman; Amin Abdul Bawa (Journal of Work-Applied Management, 2024)
Purpose – The current study aimed to examine the moderating role of perceived supervisor support in the nexus between employee empowerment and organizational commitment in the Ghanaian hospitality industry. Design/methodology/approach – A quantitative research design was adopted, and data were collected from 274 frontline workers from 4-star and 5-star hotels at two different waves within a 7-month interval. The data received were analyzed using descriptive and inferential statistics with the aid of Statistical Package for Social Sciences (SPSS V. 23.0) and SmartPLS (V.4.0), respectively. Findings – As hypothesized in the study, employee empowerment was significantly related to organizational commitment. Furthermore, the results revealed that perceived supervisor support moderated the nexus between employee empowerment and affective and continuance commitment but did not moderate the nexus between employee empowerment and normative commitment. Originality/value – Arguably, support from supervisors has been theoretically identified as a key construct in enhancing subordinates' commitment to an organization. However, less is known in the literature about the moderating role of perceived supervisory support in the nexus between employee empowerment and organizational commitment, especially in the Ghanaian hospitality industry.